The monster in the box [compact disc, unabridged] : an Inspector Wexford novel - Rendell, Ruth, 1930-2015 (Rendell, Ruth, 1930-2015. Inspector Wexford mystery., 2009)
Prolific mystery writer Ruth Rendell presents her 22nd novel featuring Chief Inspector Reginald Wexford. A seemingly typical murder leaves Inspector Wexford suspecting that the case is somehow connected to a series of old, unsolved murders. As he investigates, Wexford is haunted by memories of a killer who escaped justice many years ago.